Advance in yellowing mechanism and the regulation technology of post-harvested broccoli. Issue 3 (20th September 2020) - Luo, Feng; Fang, Huixin; Wei, Baodong; Cheng, shunchang; Zhou, Qian; Zhou, Xin; Zhang, Xuan; Zhao, Yingbo; Ji, Shujuan
Abstract: Yellowing is one of the main problems of quality deterioration in the storage, transportation, and sales of post-harvested broccoli, which seriously affects the commodity value of broccoli. Therefore, it is of significance to understand the mechanism of the process and develop effective regulation technology. In this review, we expounded the changes in the appearance of the flower ball, bud morphology, and calyx cell structure, as well as endogenous pigment metabolism, accompanying the yellowing process of broccoli. In addition, recent research on the molecular mechanism of yellowing was summarized from the aspects of transcriptome analysis and transcription regulation. Finally, the progress on the control technology of broccoli yellowing was reviewed.